Serum marker of inflammasome activity correlates with liver injury in nonalcoholic fatty liver disease and is influenced by genetic polymorphisms - Adams, L.; Wree, A.; Melton, P.; Jeffrey, G.; Ching, H.; de Boer, B.; Olynyk, J.; Ayonrinde, O.; Mori, T.; Beilin, L.; Price, Patricia; Pennell, C.; et al. (2015)
Background and Aims: The NLRP3 inflammasome has been implicated in the pathogenesis of liver injury in nonalcoholic fatty liver disease (NAFLD). In humans, mutations of Nlrp3 have functional consequences and result in auto-inflammatory syndromes. We examined whether single nucleotide polymorphisms (SNP’s) of the NLRP3 and CARD8 genes of the NLRP3 inflammasome influenced serum inflammatory markers and fatty liver in a general population based cohort. Secondly, we examined serum caspase-1 as a novel marker of liver injury and determined the association between inflammasome SNP’s, serum caspase-1 and liver injury. Methods: Inflammatory markers (CRP, IP-10, TNFR1, TNFR2, IL18), liver enzymes and ultrasound diagnosed fatty liver were assessed in a popula - tion-based cohort (n=1046) of 17-year old adolescents. Serum caspase-1 activity and protein levels were determined in a second cohort (n=154) and sub-group (n=20) of subjects with biopsy proven NAFLD by flourometric assay (Abcam, Cam - bridge, MA) and western blot respectively. Liver histology was evaluated according to the NASH CRN scoring system. Eleven NLRP3 and CARD8 SNPs were genotyped in both cohorts and assessed for phenotypic associations. Results: In cohort 1, the rs2043211 SNP in the CARD8 gene was associated with serum levels of IP10 (p=0.002), IL18 (p=0.009), sTNFR1 (p=0.04), sTNFR2 (p=0.04), CRP (p=0.056) and a diagnosis of fatty liver (adj. odds ratio 1.65, 95% CI 1.09-2.48, dominant allelic model). Serum IP10 and TNFR2 levels but not SNP genotypes were positively correlated with hepatic aminotransaminase levels. In cohort 2, serum caspase-1 activity was significantly increased in the presence of hepatocellular ballooning, inflammation and fibrosis (p<0.05 for all). The accuracy at predicting inflammation, ballooning or advanced fibrosis was modest with area under the receiver operator characteristic curves of 0.62 (95% CI 0.52-0.71), 0.58 (95% CI 0.49-0.67) and 0.66 (0.55-0.76) respectively. Serum caspase-1 p10 protein levels were also significantly higher in subjects with NASH compared to controls or simple steatosis (p=0.003). Rs2043211 was not associated with altered serum caspase-1 levels (p=0.14) or severity of liver injury or fibrosis. Rs10754558 was associated with reduced serum caspase-1 activity (p=0.03) but not alterations in liver injury or fibrosis. Conclusions: Genetic poly - morphisms in the NLRP3 inflammasome associate with altered serum inflammatory markers and risk of fatty liver in the general population, but they do not influence severity of liver injury in NAFLD. Serum caspase-1 activity may represent a novel non-invasive marker of disease severity in NAFLD.